2020
DOI: 10.2147/rmhp.s286488
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hepatitis B Vaccination Uptake Rate and Predictors in Healthcare Professionals of Ethiopia</p>

Abstract: Introduction Healthcare professionals continue to be at risk of acquiring occupation-related hepatitis B virus infection because of noncompliance for the 3-dose primary series of hepatitis B vaccine recommended. The objective of the study was to determine the rate of and to identify the predictors of hepatitis B vaccination uptake in healthcare professionals in Ethiopia. Methods A multicenter cross-sectional survey was conducted between May 19 2018 and June 15 2018. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
1
1
1
Order By: Relevance
“…Finally, the vaccination status of the respondents was significantly associated with their occupation and the availability of HBV vaccination in the workplace (Table 5 ). This is consistent with other studies that have shown an association between HBV vaccination status and marital status [ 37 ], income [ 38 , 39 ], occupation [ 25 , 39 , 40 ], and an HBV vaccination policy at the workplace as a job entry requirement [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…Finally, the vaccination status of the respondents was significantly associated with their occupation and the availability of HBV vaccination in the workplace (Table 5 ). This is consistent with other studies that have shown an association between HBV vaccination status and marital status [ 37 ], income [ 38 , 39 ], occupation [ 25 , 39 , 40 ], and an HBV vaccination policy at the workplace as a job entry requirement [ 41 ].…”
Section: Discussionsupporting
confidence: 92%
“…Finally, the study results have presented that the vaccination status of the respondents was signi cantly associated with such variables as occupation, monthly income, marital status, and availability of testing policy in the workplace (Table 6). This is inconsistent with other studies around the world that have shown an association of Hep B vaccination status with marital status (41), income (42,44), occupation (20,43,44), and HBV vaccination policy at the workplace as a job entry requirement (45).…”
Section: Discussioncontrasting
confidence: 66%
“…Low prevalence of HBV vaccination was also found in other countries, such as Ethiopia (37.7%), 21 Sweden (40%), 22 and Pakistan (40%). 23 In these countries, the determinants of non-complete vaccination were mainly the high cost of the vaccine and the lack of information by the professionals.…”
Section: Discussionmentioning
confidence: 64%
“…Baixas prevalências da vacinação contra o VHB também foram encontradas em outros países, como Etiópia (37,7%) 21 , Suécia (40%) 22 e Paquistão (40%) 23 . Nesses países, os determinantes da não vacinação completa foram principalmente o alto custo da vacina e a falta de informação dos profissionais.…”
Section: Discussionunclassified